DISPERSÃO DE FUNGOS MICORRÍZICOS ARBUSCULARES POR MORCEGOS EM UM FRAGMENTO URBANO DE FLORESTA TROPICAL - Rodrigues Jorge, Thais Martinez; Ortêncio Filho, Henrique; Carrenho, Rosilaine (Interfaces Científicas - Saúde e Ambiente, 2021)
Associations of arbuscular mycorrhizal fungi (AMF) and plant species may occur in terrestrial and air environments and need an effective dispersal, which occurs mainly by biotic vectors. Studies on the influence of flying animals on this dispersal are scarce, thus, this study aimed to investigate the role of bats in AMF propagule dispersal and the most frequent means of transport. Analyses were performed in dorsoventral hairs and feces of bats in an urban tropical forest fragment in southern Brazil, from April to September 2018. The results were negative for the presence of spores in the hair, but spores of Glomus invermaium and Acaulospora scrobiculata were detected in feces of two bat species, evidencing that they can act as secondary spore dispersers. Efficient dispersal depends on the range extension of the dispersing species, so bats can be important dispersers of AMF, since they have the ability to fly and travel long distances.